1997
DOI: 10.1007/s004150050135
|View full text |Cite
|
Sign up to set email alerts
|

Outcome in juvenile-onset myasthenia gravis: a retrospective study with long-term follow-up of 79 patients

Abstract: Randomised and controlled treatment studies of juvenile-onset myasthenia gravis have not been published. We therefore report our retrospective analysis of 79 patients with juvenile-onset myasthenia gravis observed for as long as 30 years. The mean age at onset was 13.7 years and median follow-up 7.7 years. The initial presentation was generalised disease in 90% and ocular disease in the remaining patients. Sixty-five patients (82%) were thymectomised. In 14 of these, treatment consisted of a combination of aza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
84
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(99 citation statements)
references
References 46 publications
13
84
0
2
Order By: Relevance
“…Their patients presented mainly with ocular symptoms (84.3%) at a mean age of 4.1 years. 22 Compared with studies describing pediatric myasthenia from China, Korea, Jamaica, Europe, and India, [23][24][25][26][27] whose populations are more ethically uniform, the current study is unique in that the Canadian population is ethnically diverse. Consequently, the differences in terms of gender, age of onset, and subtype of myasthenia gravis likely reflect differences in the ethnic backgrounds and associated genetic susceptibility between the populations.…”
Section: Discussionmentioning
confidence: 99%
“…Their patients presented mainly with ocular symptoms (84.3%) at a mean age of 4.1 years. 22 Compared with studies describing pediatric myasthenia from China, Korea, Jamaica, Europe, and India, [23][24][25][26][27] whose populations are more ethically uniform, the current study is unique in that the Canadian population is ethnically diverse. Consequently, the differences in terms of gender, age of onset, and subtype of myasthenia gravis likely reflect differences in the ethnic backgrounds and associated genetic susceptibility between the populations.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of juvenile patients who present with purely ocular symptoms (Osserman grade Ia) has been reported to range widely from 27% to 93% in retrospective analyses (Table 1). 4,5,13,17,22,28,29,36,41,43 The variability in presentation appears to be somewhat dependent upon ethnicity. Several studies of Asian children have reported a substantially higher incidence of ocular presentation.…”
Section: Clinical Presentation Natural History and Demographicsmentioning
confidence: 94%
“…It has been utilized as a single immunosuppressant agent in MG since the 1970s, and large, retrospective reports support its efficacy (92). A randomized, double-blind trial demonstrated its efficacy also as a steroid-sparing agent.…”
Section: Therapeutic Mg Managementmentioning
confidence: 99%